A Giant Cutaneous Horn Projecting from Verrucous Carcinoma of Buccal Mucosa: A Rare Case Report - Singh, Priyankar (J Clin Diagn Res, 2017)
Cutaneous horn is conical shape of compact keratin that resembles a miniature animal horn. Though morphologically similar to horns in animals they are histologically very different from them. It is a circumscribed, conical, hyperkeratotic dense protrusion with epithelial cornification above the skin surface in response to a wide range of underlying benign and malignant pathological changes. Though benign, a cutaneous horn holds the potential to be premalignant or malignant. In India till now six cases has been reported with cutaneous horn at various unusual sites. We report a unique case of 52-year-old woman with a giant cutaneous horn at left oral commissure with underlying verrucous carcinoma of left buccal mucosa which is a very rare location for such lesion. Considering its malignant potential, adequate therapy requires wide excision with a tumour-free margin of at least 1 cm, particularly in the facial region where the incidence of malignancy is higher.